2021
DOI: 10.3390/biology10090823
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Prognosis in CSA-AKI Using Novel Kidney Injury Biomarkers: A Prospective Observational Study

Abstract: Background: There is a need for early diagnostic solutions for cardiac surgery associated acute kidney injury (CSA-AKI) as serum creatinine changes do not occur dynamically enough. Moreover, new approaches are needed for kidney protective strategy in patients undergoing cardiac surgery procedures; Methods: Samples of serum and urine were taken from the selected group of patients undergoing elective cardiac surgery procedures. The aim of this study was to assess the utility of specific inflammation and kidney i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the KDIGO score for the assessment of kidney failure confirmed that most human patients do not present kidney failure in this study, which is consistent with the literature [ 30 , 31 ]. Acute kidney failure or AKI during and after CPB is currently a major research challenge [ 30 , 32 , 33 ] for both biomarker and therapeutic research. AKIs are the consequence of common adverse events, including hemodilution, hemolysis, inflammation [ 34 ], neuro–hormonal changes, and vasopressor use and misuse during CPB in cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the KDIGO score for the assessment of kidney failure confirmed that most human patients do not present kidney failure in this study, which is consistent with the literature [ 30 , 31 ]. Acute kidney failure or AKI during and after CPB is currently a major research challenge [ 30 , 32 , 33 ] for both biomarker and therapeutic research. AKIs are the consequence of common adverse events, including hemodilution, hemolysis, inflammation [ 34 ], neuro–hormonal changes, and vasopressor use and misuse during CPB in cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study correspond to the Heart Institute, Hospital “das Clínicas”, Faculty of Medicine, University of São Paulo, Brazil, to compare the length of stay of patients with heart disease undergoing cardiac surgery [ 45 ]. The considered covariates are: age of the patient, type of protocol, race, sex, and type of patient.…”
Section: Application To Biomedical Datamentioning
confidence: 99%
“…In the case of fluid excess, hemofiltration should also be targeted to provide an adequate fluid balance in the post-CPB period. Intraoperative hypovolemia should be avoided though, as it has a proven detrimental impact on kidney function [115,116]. A further significant benefit of hemofiltration during the CPB is osmotic load and metabolite removal.…”
Section: Fluid Balance and Osmotic Regulationmentioning
confidence: 99%